Culling pattern and effect of selection on milk production over the periods in Sahiwal cattle at an organised farm - UPADHYAY, ARPAN; SADANA, DEVINDER KUMAR; GUPTA, ASHOK KUMAR; CHAKRAVARTY, ATISH KUMAR; SINGH, AVTAR; DASH, SOUMYA; DASH, SHAKTIKANT (The Indian Journal of Animal Sciences, 2017)
The investigation was carried out on 1,629 calving records of 462 Sahiwal cows calved between 1988 and 2013 at National Dairy Research Institute, Karnal, Haryana, India to study culling pattern as well as the effect of selection on milk production. Average culling and mortality rate per lactation of Sahiwal cows were 23.82 and 4.54%, respectively. The culling was found due to teat and udder problems (32.47%), followed by reproductive problems (22.73%) and low milk production (10.82%) in the herd. Most of the voluntary culling (based on the low milk yield) was observed during second and third lactations. Stage of lactation and milk yield had significant influence on culling during first lactation whereas, period had significant influence on culling during second lactation. Sahiwal cows yielding more than 8 kg of milk/day were less likely to cull and the probability of culling of cows increased after the completion of 360 days of first lactation. Most probable producing ability of per day milk yield [MPPA (PDMY)] was estimated for selected and culled cows. There is an intense need to minimize the involuntary culling of cows by providing better feeding and management so that more of cows can be saved in herd, which will in turn facilitate in increasing selection intensity and selection differential in the herd and ultimately help in faster genetic improvement of Sahiwal cows.